Development of a Double Caged (Active-Passive) Puddler - Kumar, Maheshwari Rakesh; E. V, Thomas (Indian Journal of Hill Farming, 2019)
Rice seedlings are usually transplanted in a puddled field. Tractor cage wheel, being usedextensively for this purpose is poorly effective and causes excessive wear on the brakes.Animal drawn puddlers have low work rate. Because of higher rotary speed, rotary tillertines wear very fast and consume excess power. A study was therefore undertaken todesign and develop a double caged (active-passive) power operated puddler. A prototypepower operated puddler of 400 mm width was designed and developed. It comprised twoconcentric cages. The inner cage was powered while the outer was dragged. Thetransmission system was developed for testing the performance of the puddler at differentrotary speeds in the range of 41 to 181 rpm. Field experiments were conducted in order toevaluate performance of the developed puddler. The newly designed puddler unit wasattached to a power tiller by replacing the conventional rotary tiller. The level of puddlingwas varied from single pass to three passes. The whole experiment was also conductedwithout dragged cage in the newly designed puddler. To compare the performance, aconventional power tiller operated rotary tiller was tested at available two rotary speeds.With increased rotary speed as well as number of passes puddling index of the developedpuddler was found increasing. When the developed puddler was operated without draggedcage, the fuel consumption was found to be higher as compared to that with dragged cage.The developed puddler with dragged cage was found to be 14.5% and 30.5% fuel savingagainst power tiller operated rotary tiller, for 65.0 and 80.0 % puddling index, respectively.